2016
DOI: 10.1016/j.jtho.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Custom Gene Capture and Next-Generation Sequencing to Resolve Discordant ALK Status by FISH and IHC in Lung Adenocarcinoma

Abstract: Background-We performed a genomic study in lung adenocarcinoma cases with discordant anaplastic lymphoma kinase (ALK) status by fluorescent in situ hybridization (FISH) and immunohistochemistry (IHC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…14 No morphologic parameter could be identified that correlated with the presence of V3 in tumor biopsies of ALK 1 NSCLC patients. 18,31,32 Upfront NGS testing in particular is a time-efficient and material-sparing strategy for parallel detection of actionable genetic alterations in NSCLC with failure rates of approximately 10%, 18 which is considerably lower than the 32%-50% drop-out rate in the detection of ALK fusion variants observed in the current and other studies after serial application of different methods on the limited material obtained from small biopsies. These methods, however, are not part of the current diagnostic guidelines, which prioritize ALK IHC and FISH.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 68%
“…14 No morphologic parameter could be identified that correlated with the presence of V3 in tumor biopsies of ALK 1 NSCLC patients. 18,31,32 Upfront NGS testing in particular is a time-efficient and material-sparing strategy for parallel detection of actionable genetic alterations in NSCLC with failure rates of approximately 10%, 18 which is considerably lower than the 32%-50% drop-out rate in the detection of ALK fusion variants observed in the current and other studies after serial application of different methods on the limited material obtained from small biopsies. These methods, however, are not part of the current diagnostic guidelines, which prioritize ALK IHC and FISH.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 68%
“…The authors identified false‐negative FISH samples and concluded that ALK testing should initially be based on IHC and/or NGS‐based methods instead of FISH testing . Finally, Jang et al conducted a similar study and found that ALK FISH results were false‐positive in three out of four FISH‐positive/IHC‐negative cases and confirmed that NGS approach was most effective in detection of ALK rearrangements …”
Section: Discussionmentioning
confidence: 95%
“…As mentioned earlier, this case probably represents a false positive ALK FISH result. It has been shown recently that NGS studies might be of help in resolving discordant ALK status cases …”
Section: Discussionmentioning
confidence: 99%
“…5 Other methods for detection of ALK rearrangement status reported extensively in the literature include immunohistochemistry (IHC), [6][7][8][9][10][11][12][13] reverse transcription-polymerase chain reaction (RT-PCR) 14,15 and, more recently, next-generation sequencing. 10,16,17 In 2013, the College of American Pathologists (CAP), the Association for Molecular Pathology (AMP) and the International Association for the Study of Lung Cancer (IASLC) guideline for molecular testing in lung adenocarcinoma recommended ALK FISH testing as a standard method for detection of ALK rearrangements. 5 The same guideline suggests ALK IHC as an alternative method for the screening of ALK rearrangement status.…”
Section: Introductionmentioning
confidence: 99%